Beyond the page - Coulter, Myrl (Canadian literature, 2011)
Teenage runaway Lily "flashes on the little tree frogs that used to cling to the siding under her bedroom window" and damaged war veteran Stephen "flashes on a pair of prints," two paintings from his childhood home. From the teenage runaway with an undeniable instinct for survival, to the damaged boy who becomes the novel's anguished villain, to the veterinary technician who still mourns the loss of her lesbian partner, Fauna's characters propel the novel's various storylines to the end of its week and beyond.